Farmers’ Willingness to Accept a Compensation to Protect Agricultural Land Sustainability in Peri-Urban Areas of Pekalongan City - Imade Yoga Prasada; Masyhuri Masyhuri (Agro Ekonomi, 2019)
Agricultural land is a land that has a relatively low rental value, so agricultural land is very vulnerable to be converted. Therefore, this research was conducted with the aim 1) to know farmers’ willingness to accept a compensation to protect agricultural land sustainability, 2) to know the factors that influence farmers' willingness to accept / reject WTA, and 3) to know the factors that influence the WTA value of farmers’ in the peri-urban areas. The study was conducted in the peri-urban areas of Pekalongan City. The research respondents were 90 farmer owners and cultivators. The research data was analyzed by using Heckman's two-stage model. The results showed that farmers’ WTA in the peri-urban areas of Pekalongan City amounted to IDR 7,217,827.27 per year. Factors that influence farmers’ willingness to accept or reject compensation are the distance of the agricultural land to the main road and farmers' perceptions toward the sustainability of agricultural land in the peri-urban areas. Factors that influence the number of farmers’ WTA to be willing to protect the agricultural land in the peri-urban areas of Pekalongan City are farmers’ farm income and farming experience of the farmers. Sustainability of agricultural land in the suburbs of Pekalongan City can be maintained by taking into account the facilities and infrastructure needed by farmers who own agricultural land both far and close to the main road, increasing farmers' perceptions of the sustainability of agricultural land, increasing farm income and reducing the risk of farming production.